FOAM SCLEROTHERAPY: AN EMERGING, MINIMALLY INVASIVE AND SAFE MODALITY OF TREATMENT FOR VARICOSE VEINS - Kharl, Rai Ahmad Khan; Khan, Nauman Imtiaz; Pervaiz, Hafiz Khalid; Ali, Kishwar; Haider, Fazal e; Sattar, Saim; Ahmad, Zubair; Nasir, Muhammad; Bajwa, Mubashir; Siddique, Afzal (Journal of Ayub Medical College Abbottabad, 2019)
Background: Ultrasound guided foam sclerotherapy is an outdoor, office based and minimally invasive procedure for the treatment of varicose veins. This study was carried out to highlight the potential of foam sclerotherapy as a first line treatment for varicose vein. Methods: This prospective observational study was conducted at CMH Rawalpindi, form 1 Aug 2017 to 30 Aug 2018The demographic and outcome data of the patients, who underwent ultrasound guided foam sclerotherapy, were collected and analysed. Results: A total of 662 patients and 752 legs were treated with foam sclerotherapy. Four hundred and ten (61.93%) were males and 252 (38.06%) were females. Their ages ranged from 17 to 68 years with the mean age of 43.21 years. Six hundred and sixty-eight (88.82%) legs were having Great Saphenous Vein while 84 (11.17%) legs were having short saphenous vein disease. Maximum legs 256 (34.04%) had C3 disease. single session of Foam sclerotherapy was enough in 511 (67.95%) legs, while 197 (26.19%) legs were treated with two and 44 (5.85%) legs were treated with three sessions of foam sclerotherapy. Percentages of main trunk occlusion were 98.01% at 1 month while 97.39% at 3 months follow up. Only 2 (0.30%) patients had Deep Venous Thrombosis while 3 (0.45%) patients had thrombophlebitis which required surgery. Conclusion: Ultrasound Guided Foam sclerotherapy is an OPD based, innovative, minimally invasive and safe method of treatment for varicose veins. In the context of prevalence of varicose vein disease in our community, it relieves the Burdon of operation theatre list and creates the theatre space for vascular surgeon for arterial Surgery. Keywords: Ultrasound Guided Foam Sclerotherapy; UGFS; Varicose veins